Mitochondrial Reactive Oxygen Species Formation Determines ACSL4/LPCAT2-Mediated Ferroptosis - Melanie Merkel; Bjarne Goebel; Moritz Boll; Aasha Adhikari; Viktoria Maurer; Dieter Steinhilber; Carsten Culmsee (MDPI AG, 2023)
Ferroptosis is a form of oxidative cell death that is characterized by enhanced lipid peroxidation and mitochondrial impairment. The enzymes acyl-CoA synthetase long-chain family member 4 (ACSL4) and lysophosphatidylcholine acyltransferase (LPCAT) play an essential role in the biosynthesis of polyunsaturated fatty acid (PUFA)-containing phospholipids, thereby providing the substrates for lipid peroxidation and promoting ferroptosis. To examine the impact of mitochondria in ACSL4/LPCAT2-driven ferroptosis, HEK293T cells overexpressing ACSL4 and LPCAT2 (OE) or empty vector controls (LV) were exposed to 1S, 3R-RSL3 (RSL3) for induction of ferroptosis. The ACSL4/LPCAT2 overexpression resulted in higher sensitivity against RSL3-induced cell death compared to LV-transfected controls. Moreover, mitochondrial parameters such as mitochondrial reactive oxygen species (ROS) formation, mitochondrial membrane potential, and mitochondrial respiration deteriorated in the OE cells, supporting the conclusion that mitochondria play a significant role in ACSL4/LPCAT2-driven ferroptosis. This was further confirmed through the protection of OE cells against RSL3-mediated cell death by the mitochondrial ROS scavenger mitoquinone (MitoQ), which exerted protection via antioxidative properties rather than through previously reported metabolic effects. Our findings implicate that mitochondrial ROS production and the accompanying organelle disintegration are essential for mediating oxidative cell death initiated through lipid peroxidation in ferroptosis.